PENGARUH PERTUMBUHAN EKONOMI DAERAH, DANA BAGI HASIL, DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN BELANJA DAERAH (Studi pada Pemerintah Kota di Provinsi Aceh) - Shara Amelia Putri; Surya Darni (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study is to determine the impact of regional economic growth, revenue-sharing funds, general distribution funds, and local revenue growth on regional spending growth. The study analyzed data by multiple linear regression and was conducted in 23 district/municipal governments in Aceh. The results show that regional economic growth, revenue-sharing funds, general distribution funds, and regional revenue growth simultaneously and partially affect regional spending growth. These results suggest that increases in regional spending are likely to occur as a result of higher local income levels and economic growth